The Ethical climate at Workplace Environment and its Impact on Job InsecurityApplied Study for the Public Energy Production Management Office at Al- Furat Al- Awsat Region - Al- salami, Yamama Mudhher Azawi (Journal of Economic, Administrative and Legal Sciences, 2019)
The ethical climate impacts the workers’ behavior and the performance effectiveness. It establishes the values that dominate the woke environment.The research aims to identify the importance of the moral atmosphere which dominates the public energy production management office at Al- Furat Al- Awsat Region for under contract workers.The research measures the job insecurity which could be affected by this atmosphere.The results of this research proofed that the moral atmosphere has a major impact on job insecurity workers’ feelings at both the quantitive and the qualitative on an unequal rate.
Keywords: ethical climate; work environment; job insecurity